Influências interlinguísticas na fala e na escrita de crianças bilíngues falantes do português e do Hunsrückisch : consoantes oclusivas, fricativas e róticas - Martins, Rosemari Lorenz (2013)
This thesis has as its central theme the inter-linguistics influences, by phoneticphonological order, involving plosive, fricative and rhotic consonants of Brazilian Portuguese (BP) in speech and writing of by bilingual children, speakers of Hunsrückisch (HR) and BP, in the rural and urban areas of the town of Morro Reuter/RS in the acquisition phase of writing. Two research questions have emerged from this theme: (i) to what extent does the child in the writing acquisition phase draw on their own speech when writing? (ii) Is bilingualism the only cause for exchanges in their orthographic exchanges analyzed in bilingual children? In order to contribute to the discussion on these issues, it has been established as a general objective to investigate the trading of plosive, fricative and rhotic consonants in the speech and writing of bilingual children based on the processes of: a) voicing process, b) devoicing process, c) neutralization, and d) potentiation. The aim is also to identify the role of linguistic contexts and the influence of years of education, sex and area of residence of respondents (rural and urban) in each case. Therefore, we investigated the speech and writing of 36 bilingual children, in the 1st, 2nd and 3rd year of elementary school in the city of Morro Reuter/RS, the speech of their parents and grandparents. Beside this, we investigated also the writing of 36 monolingual children, in the 1st, 2nd and 3rd year of elementary school in the city of Novo Hamburgo/RS. The analysis of the speech and writing samples showed that the most frequent exchange processes, both in speech and writing, are neutralization and devoicing process. The analysis also showed that the exchange processes analyzed in both language modalities are the same, thus indicating that children in the acquisition phase draw to a certain extent on speech when initializing writing. The highest exchange percentages in all the processes in the writing sample combined with the fact the same processes have also been found on the writing sample of monolingual children, who don t exchange in speech, suggests, however, that the exchanges in writing may be also related to the strategies which are used by kids in order to acquire writing. After all, this analysis showed that the respondents from rural area exchange more than the respondents from urban area, because their social network are a little more dense and multiplexing than the social network of the respondents from urban area, which is a little more weak and less multiplex. Regarding the phonetic-phonological processes studied, we noted that the processes of voicing process, devoicing process and neutralization in speech may result from inter-linguistics influences of HR on BP. However, the exchanges in writing may also happen duo to difficulties related to orthography and to other difficulties related to the process of writing acquisition.